2021
DOI: 10.1002/ncp.10760
|View full text |Cite
|
Sign up to set email alerts
|

Blenderized food tube feeding in patients with head and neck cancer

Abstract: Background Patients with headand neck cancer (HNC) are at high risk for malnutrition before and during chemoradiation treatment. Many will also require tube feeding to address declines in energy intake, weight, and quality of life (QOL) caused by the impact of treatment on gastrointestinal (GI) symptoms. Blenderized tube feeding (BTF) may ameliorate these adverse conditions. Methods In this open‐label, prospective pilot study, 30 patients with HNC who required feeding tube placement were recruited to switch fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…48 Furthermore, a prospective observational cohort study reported significant decrease in diarrhoea post-BD intervention (either homemade BD or commercial sterile BD) using the PedsQL GIS Scale (from 87.9 to 73.6, p = 0.004). 46 Further evidence of improved symptoms of diarrhoea on BD is found in an open-label, prospective pilot study of adults with head and neck cancer by Spurlock et al 49 This study was published after searches were concluded, and the findings are congruous with this review. 49 This small yet compelling study found 37.5% of participants (n = 16) reported diarrhoea on CFF, reducing to 0% on transition to BD.…”
Section: Bd May Improve Symptoms Of Diarrhoea In Patients Who Are Ent...mentioning
confidence: 79%
See 2 more Smart Citations
“…48 Furthermore, a prospective observational cohort study reported significant decrease in diarrhoea post-BD intervention (either homemade BD or commercial sterile BD) using the PedsQL GIS Scale (from 87.9 to 73.6, p = 0.004). 46 Further evidence of improved symptoms of diarrhoea on BD is found in an open-label, prospective pilot study of adults with head and neck cancer by Spurlock et al 49 This study was published after searches were concluded, and the findings are congruous with this review. 49 This small yet compelling study found 37.5% of participants (n = 16) reported diarrhoea on CFF, reducing to 0% on transition to BD.…”
Section: Bd May Improve Symptoms Of Diarrhoea In Patients Who Are Ent...mentioning
confidence: 79%
“…49 This small yet compelling study found 37.5% of participants (n = 16) reported diarrhoea on CFF, reducing to 0% on transition to BD. 49 Tellingly, all participants elected to remain on BD thereafter, and those reporting 'good' or 'very good' quality of life increased from 50.1% before to 91.3% after BD intervention. 49 The quality of life of people who are enterally fed may be negatively affected by GIS such as diarrhoea, therefore optimising symptom control is a logical step.…”
Section: Bd May Improve Symptoms Of Diarrhoea In Patients Who Are Ent...mentioning
confidence: 93%
See 1 more Smart Citation
“…These concerns may be due in part to the fact that most published studies report high bacterial contamination in BTF, but these findings have been challenged in two recent articles showing that BTF can be safely prepared in the hospital and home environment 9,10 . In spite of concerns by healthcare professionals, emerging research has corroborated the anecdotal reports of patients and caregivers attesting that BTF reduces tube feeding intolerance (gagging, retching, vomiting, diarrhea, constipation, and volume intolerance), supports weight/growth goals, increases oral intake in patients deemed safe for swallowing, reduces infection and hospitalization, and provides a more physiologic feeding 21–28 . Consequently, research on methods of minimizing risk of microbial infection in the HEN population is paramount, particularly for those using HBTF.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In spite of concerns by healthcare professionals, emerging research has corroborated the anecdotal reports of patients and caregivers attesting that BTF reduces tube feeding intolerance (gagging, retching, vomiting, diarrhea, constipation, and volume intolerance), supports weight/growth goals, increases oral intake in patients deemed safe for swallowing, reduces infection and hospitalization, and provides a more physiologic feeding. [21][22][23][24][25][26][27][28] Consequently, research on methods of minimizing risk of microbial infection in the HEN population is paramount, particularly for those using HBTF.…”
Section: Discussionmentioning
confidence: 99%